Penerapan Literasi Digital di Kalangan Biarawan - Terra, Heinrich; Lewi Pramesti, Olivia (Jurnal InterAct, 2024)
Digital literacy competence needs to be possessed by monks even though they experience limitations in the use of digital media in their daily lives. The purpose of this research is to determine the application of digital literacy competence among catholic monks of generations Y and Z. The theory used is the ten digital literacy competencies according to the Jaringan Pegiat Literasi Digital (Japelidi) or Digital Literacy Activist Network. This research uses a qualitative descriptive method with a comparative study approach. The research subjects are catholic monks of the Ordo Fratrum Minorum (OFM) from generations Y and Z in the Community of St. Bonaventure Monastery, Yogyakarta. There are five monks who interviewed by author. The results show that monks of generation Y are only unable to apply collaborative competence, while monks of generation Z are unable to apply analytical, distributive, and collaborative competencies.